2014
DOI: 10.1093/jjco/hyu178
|View full text |Cite
|
Sign up to set email alerts
|

Effect of liver cirrhosis on metastasis in colorectal cancer patients: a nationwide population-based cohort study

Abstract: Objective: The aim of this study is to evaluate the liver metastasis risk among colorectal cancer patients with liver cirrhosis. Methods: This was a nationwide population-based cohort study of 2973 newly diagnosed colorectal cancer patients with liver cirrhosis and 11 892 age-sex matched controls enrolled in Taiwan between 2000 and 2010. The cumulative risk by Kaplan-Meier method, hazard ratio by the multivariate Cox proportional model and the incidence density were evaluated. Results: The median time interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 26 publications
(30 reference statements)
1
19
1
Order By: Relevance
“…Although liver metastasis can occur in CRC patients without NAFLD, a recent large prospective human cohort analyzing 2,715 CRC patients with liver metastasis as well as other retrospective studies have suggested that the patients with NAFLD have an increased risk of liver metastasis and for the recurrence of liver metastasis after resection, when compared with patients without NAFLD . Moreover, higher recurrence rate of liver metastasis in patients with fibrosis have also been reported in recent studies . However, previous studies underestimated the risk of liver metastasis or have reported contradictory results in patients with underlying fatty liver and fibrosis .…”
Section: Discussionmentioning
confidence: 96%
“…Although liver metastasis can occur in CRC patients without NAFLD, a recent large prospective human cohort analyzing 2,715 CRC patients with liver metastasis as well as other retrospective studies have suggested that the patients with NAFLD have an increased risk of liver metastasis and for the recurrence of liver metastasis after resection, when compared with patients without NAFLD . Moreover, higher recurrence rate of liver metastasis in patients with fibrosis have also been reported in recent studies . However, previous studies underestimated the risk of liver metastasis or have reported contradictory results in patients with underlying fatty liver and fibrosis .…”
Section: Discussionmentioning
confidence: 96%
“…A recent report showed that liver metastasis risk was underestimated and it was even higher in patients with CRC with cirrhosis of the liver [ 14 ]. In the report, however, neither diagnostic modalities for liver metastasis nor occurrence of HCC were specified.…”
Section: Discussionmentioning
confidence: 99%
“…Aging may also contribute to changes in liver tissue stiffness, as well as increase the likelihood of tissue fibrosis following an acute injury or illness [8][9][10]. The literature on the effect of such biomechanical alterations on tumor growth in the liver is seemingly inconsistent: some report low incidence of CRC metastases in cirrhotic livers (with accompanying fibrosis) [11], while others have reported that the risk of CRC liver metastases may be higher in patients with cirrhosis [12]. Still others report that stiff tissues can promote tumor growth and metastasis in the liver (e.g., [13]).…”
Section: Introductionmentioning
confidence: 99%